Outcomes following early red blood cell transfusion in acute upper gastrointestinal bleeding. - Hearnshaw, SA; Logan, R; Palmer, K; Card, T; Travis, S; Murphy, M (2010)
BACKGROUND: Acute upper gastrointestinal bleeding (AUGIB) accounts for 14% of RBC units transfused in the UK. In exsanguinating AUGIB the value of RBC transfusion is self evident, but in less severe bleeding its value is less obvious. AIM: To examine the relationship between early RBC transfusion, re-bleeding and mortality following AUGIB, which is one of the most common indications for red blood cell (RBC) transfusion. METHOD: Data were collected on 4441 AUGIB patients presenting to UK hospitals. The relationship between early RBC transfusion, re-bleeding and death was examined using logistic regression. RESULTS: 44% were transfused RBCs within 12 hours of admission. In patients transfused with an initial haemoglobin of <8 g/dl, re-bleeding occurred in 23% and mortality was 13% compared with a re-bleeding rate of 15%, and mortality of 13% in those not transfused. In patients transfused with haemoglobin >8 g/dl, re-bleeding occurred in 24% and mortality was 11% compared with a re-bleeding rate of 6.7%, and mortality of 4.3% in those not transfused. After adjusting for Rockall score and initial haemoglobin, early transfusion was associated with a two-fold increased risk of re-bleeding (Odds ratio 2.26, 95% CI 1.76-2.90) and a 28% increase in mortality (Odds ratio 1.28, 95% CI 0.94-1.74). CONCLUSIONS: Early RBC transfusion in AUGIB was associated with a two-fold increased risk of re-bleeding and an increase in mortality, although the latter was not statistically significant. Although these findings could be due to residual confounding, they indicate that a randomized comparison of restrictive and liberal transfusion policies in AUGIB is urgently required.